(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
The degree of salinity of the agricultural lands of Armavir and Baghramyan Regions was evaluated. Soil samples were collected from 66 agricultural lands, which are almost evenly distributed in Armavir and Baghramyan Regions, at the end of the irrigation season (October) in 2023․ To determine the degree of salinity, the electrical conductivity of the samples was the primary indicator assessed. The study’s findings indicate that there was a notable buildup of soluble salts in the upper soil horizons, which potentially decreased soil productivity. Considering this, it is crucial to manage the region’s soils sustainably and with constant observation.